Growth regulators influence on stability of shoots and ascorbic acid content at cadmium and nickel joint action - Artiushenko, T. A.; Grishko, V. M. (Acta Agraria Debreceniensis, 2016)
It is shown that for a maize the most effective protector of cadmium and nickel influence was zeastimulin, for a pea – agrostimulin.A protective function of emistim C for both cultures was insignificant. It is set that zeastimulin is influential in the increased metals absorption of a root system, however substantially (on 15% for a nickel and twice for a cadmium) reduces their translocation to above-ground part of plants. Previous treatment of pea seed by agristimulin also intensified the accumulation of nickel roots on 60% and did not influence on cadmium absorption and toxicants translocation to tissues of assimilatory organs. The protector role of growth regulators to cadmium and nickel joint influence shows up in the increase of ascorbic acid maintenance in the roots cells of both species to 34%, where as in leaves – at a maize resulted in the lowering of vitamin С amount (on 28%), but at a pea – increase on 20%.